Regional specialization and diversification of industries in Kazakhstan - Alibekova, Gulnaz; Alzhanova, Farida; Osmanov, Zhasym; Omarov, Akedil (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This research aims to assess the degree of specialization and diversification in the regions of Kazakhstan. The method of calculating the location quotient is used to determine the degree of specialization of the regions. The industrial location quotient for three periods - 2010, 2015, and 2019 - is calculated to observe the dynamics of specialization of industries in the regions. The research identified sustainable, unstable, fading, and emerging. The degree of industrial diversification in the region is determined based on the number of sustainable industries in the region. The categorization of industries according to the dynamics of specialization makes it possible to apply various mechanisms and ways to recover fading industries and support unstable and emerging industries. The research results can be used in designing Kazakhstan's regional industrial and innovation policies.